1998
DOI: 10.1002/(sici)1096-9098(199805)68:1<48::aid-jso10>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

CMF + radiotherapy in the primary treatment of operable breast cancer: Preliminary results of a phase II pilot study

Abstract: Background and Objectives: Chemotherapy and radiotherapy have been investigated in several studies about their role in primary (neoadjuvant) treatment before surgery in breast cancer. We proposed a pilot study to evaluate a primary scheme of alternate radio‐chemotherapy in the treatment of operable (T2‐ small T3) breast cancer. Methods 14 patients were recruited. Cyclophosphamide, methotrexate, and 5‐fluorouracil (CMF) were administered on days 1 and 8, every 4 wk, for two cycles. Radiotherapy was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Within this algorithm, the patients are treated with preoperative neoadjuvant chemotherapy and then with radiation before the mastectomy. Numerous reports have shown that this is oncologically safe . The chemotherapy regime is tailored according to tumour markers and biology in the usual fashion and is not altered by this new protocol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this algorithm, the patients are treated with preoperative neoadjuvant chemotherapy and then with radiation before the mastectomy. Numerous reports have shown that this is oncologically safe . The chemotherapy regime is tailored according to tumour markers and biology in the usual fashion and is not altered by this new protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have shown that this is oncologically safe. [15][16][17][18][19][20][21] The chemotherapy regime is tailored according to tumour markers and biology in the usual fashion and is not altered by this new protocol. The radiotherapy is given as described in Methods section.…”
Section: Introductionmentioning
confidence: 99%
“…Our group suggests that those who would normally be offered neoadjuvant chemotherapy and adjuvant radiotherapy instead have both treatments in the neoadjuvant setting prior to mastectomy at which immediate free autologous reconstruction (TRAM/DIEP) is also performed. Of the few similar trials published with small numbers of patients with LABC treated by neoadjuvant chemotherapy followed by preoperative radiotherapy, none have included free autologous/perforator flap reconstruction as an end point for assessment . We propose a strategy to evaluate this combined cancer management and reconstructive pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Attempting to increase breast conservation, some trials have evaluated neoadjuvant chemotherapy followed by preoperative radiotherapy. The rationale is to achieve synergistic cytotoxicity with higher complete pathological response rates . It remains unknown whether pathological responses from chemotherapy alone are similar to those achieved with synchronous and sequential preoperative radiotherapy, but it has been observed that only trials comparing variable treatment sequencing can address this question …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation